2018
DOI: 10.1155/2018/6251321
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptional Case of Ileocolic Intussusception Secondary to Burkitt’s Lymphoma: What Variations Are There in the Presentation and Management of Those Patients Who Approach Adolescence?

Abstract: Intussusception is a common cause of abdominal pain among the paediatric population with up to 10% of cases occurring secondary to a pathological lead point. Burkitt's lymphoma (BL) is a highly malignant and rapidly growing B-cell neoplasm which in extremely rare cases can present as intussusception. We report a case in an otherwise healthy 15-year-old male who presented with atypical abdominal pain. Imaging subsequently indicated an ileocolic intussusception, and given that the suspicion of a pathological lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
2
5
0
3
Order By: Relevance
“…Most of the cases in children affect the distal ileum/ ileocecal region. [15] Similar findings have been reported by Krish Kulendran et al [16] that shows similar findings in our study too. The intestine is the most common site of primary extranodal lymphoma, [17] the usual clinical presentation is abdominal pain and a palpable right lower quadrant mass.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the cases in children affect the distal ileum/ ileocecal region. [15] Similar findings have been reported by Krish Kulendran et al [16] that shows similar findings in our study too. The intestine is the most common site of primary extranodal lymphoma, [17] the usual clinical presentation is abdominal pain and a palpable right lower quadrant mass.…”
Section: Discussionsupporting
confidence: 92%
“…presence of a lymphoma is often observed and therefore in these cases surgery should be followed by chemotherapy. In the present case, a Burkitt's lymphoma (BL), which is a highly malignant and rapidly growing B-cell neoplasm [1] was histologically diagnosed. BL is a highly aggressive disease invading bone marrow in 35% of cases and central nervous system in 15% of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Intussuception is a common condition in children, especially in those aged between 4 and 5 years old, due to a congenital laxity of mesentery, and often represents a cause of intestinal obstruction. It is called primary idiopathic intussusception in children and it is mostly treated by air enema reduction [1].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their location, intussusceptions have been classified into four categories: (1) those confine to the small bowel (entero-enteric) (2) those, involving the large bowel only (colo-colic), ( 3) ileo-colic, that occurs as the prolapse of the terminal ileum within the ascending colon and (4) ileo-cecal, when the ileo-cecal valve acts as a lead point of the intussusception. While colo-colonic intussusception is predominately caused by malignancy (70% of cases), 70% of small intestine intussusceptions are caused by a benign pathology [1,5,7,9] . Considering the pathological causes of intussusception in the present study, four cases were secondary to diffuse large B cell lymphoma (DLBCL), however Yakan S et al [1] has reported one case of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 90% of cases occur in the small or large bowel and the remaining 10% involve the stomach or surgically created stomas. Computerized tomography (CT) is often considered as one of the most useful, sensitive imaging modality in the diagnosis of intussusception [1,6,7] .…”
Section: Introductionmentioning
confidence: 99%